Laboratory investigation of chewing gum - Belt, Simon (The University of Hull)
A laboratory-based investigation into the chemical flavourings found in chewing gum. The investigation is based around some 'problem' gum and the students are set the challenge of solving the problem. Students contribute to experimental design and carry out extractions, purifications and analysis of purified extracts by GC and/or GC-MS.